Controlling shareholders’ networks and related party transactions : moderating role of director remuneration in Malaysia - Mohd Mohid Rahmat; Hanis Amera Mohd Amin; Norman Mohd Saleh (Penerbit Universiti Kebangsaan Malaysia, 2018)
Past research argued that controlling shareholders can use their power of control to influence their networks via proxy (CSProxy) and multiple-directorship (CSMulti) to engage in related party transactions (RPT). Thus, we examine the associations between CSProxy and CSMulti, and RPTs. Additionally, directors are rewarded with remunerations, and therefore, director remuneration may be effective in minimizing agency conflict. Thus, we examine the impact of director remuneration as a moderator of the relationships between CSProxy and CSMulti, and RPT. The hypotheses are tested using a sample that consists of 622 listed companies in Malaysia over the period 2012-2014 with a total of 1,866 observations. CSProxy and CSMulti are found to have positive associations with RPTs. We also find that director remuneration is significant in moderating the CSProxy and CSMulti, and RPT relationships. This evidence suggests that director remuneration is an effective monitoring cost to minimize the abuse of RPTs by opportunistic controlling shareholders via their networking, CSProxy and CSMulti. It raises the concerns of the regulators and policy makers that controlling shareholders may utilize their posts, power, position and networks to opportunistically expropriate firm resources. Firm’s remuneration committee has to understand the importance of determining attractive remuneration that fulfils directors’ expectation and satisfaction.